Pengaruh Kualitas Produk, Harga dan Promosi terhadap Loyalitas Pelanggan melalui Kepuasan Pelanggan sebagai Variabel Intervening pada Kartu Prabayar Xl Axiata di Surabaya - Tambunan, Boston; Prabowo, Budi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The reason of the comes about of this consider is to educate the affect of item quality, cost and promoting on client dependability through client fulfillment as an interceding variable for Surabaya's XL Axiata paid ahead of time card. Employing a information examination procedure, way investigation, he tests 100 individuals. The information investigation utilized was different straight relapse examination utilizing SPSS 25. Theory test comes about appear that item quality, cost, and promoting have positive and critical impacts on client fulfillment, whereas client dependability is impacted by client fulfillment. Mediating fluctuating item quality, cost, and client fulfillment have positive and critical impacts, whereas publicizing has no critical impact.